Correlates of alienation among selected Jamaican adolescents - Stokes, Blossom O'M (1984)
This study examined alienation, expressed as feelings of powerlessness, normlessness, and social isolation, among 769 Jamaican adolescents, and attempted to determine which of the selected variables best predicted and explained feelings of alienation. Sampling was carried out in two phases: Phase 1 in 1980 consisted of 310 Grade 11 students (159 boys, 151 girls) from Montego Bay, and Phase 2, sampled in 1983, consisted of 217 students (94 boys, 123 girls) from Montego Bay and 242 (112 boys, 120 girls) from Kingston. A battery of tests was used to collect the data. Statistical analysis of the data revealed that: 1) alienated individuals placed a high value on occupational primacy, were low trusters, non-activists, had poor self-concepts, a negative attitude towards religion, and a greater integration with relatives. Low birth order and socio-economic status, as well as high achievement motivation were also characteristic of alienation. Girls were more alienated than boys; 2) for Sample 1, there were no significant differences in alienation scores between adolescents whose attitudes were typical of their school mates and those who held differing views. For Samples IIA and IIB, however, significant differences existed; and 3) there were significant differences on sex and school type for those variables which correlated significantly with alienation. Interaction between sex and school-type emerged for the variables Life-Style and Occupational Primacy
Keywords: Social alienation